Compressive strength of concrete: A review -Nicaragua case - Francisco Hernández, Eddisson (2025)
Concrete is a composite material conformed of cement paste and aggregates, which, depending on the materials and proportions used, has different properties both in the fresh and hardened state. According to the state of the art, compressive strength is the property specified to determine its quality at 28 days, which is in function of some factors such as the cement hydration process, types and sized of aggregates, proportion of materials and curing conditions. In this work, through a documentary review, the analysis and assessment of the factors that affect the properties of concrete elaborate in Nicaragua are presented, using data on the physical properties of the materials, mix design and compressive strength, obtained in laboratory and field. Highlighting as the most relevant: the type of cement, type and maximum size of aggregate, cement/aggregate and coarse aggregate/fine aggregate, ratios.